2007
DOI: 10.1002/ajmg.a.31561
|View full text |Cite
|
Sign up to set email alerts
|

Branchio‐oto‐renal syndrome

Abstract: Branchio-oto-renal syndrome, a phenotype consisting of hearing loss, auricular malformations, branchial arch remnants, and renal anomalies is now recognized as one of the more common forms of autosomal dominant syndromic hearing impairment. Three loci known to be associated with the BOR phenotype have been identified and two genes that act in a regulatory network have been cloned, EYA1 and SIX1. EYA1 and SIX1 are homologous to genes involved in Drosophila eye development, eyes absent gene (eya), and sine oculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 55 publications
3
108
0
3
Order By: Relevance
“…The identification of such a programme could improve our understanding of the HOXA2 mutant phenotype in humans. Indeed, we have shown that Hoxa2 regulates the expression of Eya1, which is involved in the branchio-oto-renal syndrome in humans (Abdelhak et al, 1997;Kochhar et al, 2007). Our functional and molecular analyses also reveal that Hoxa2 is involved in the regulation of Bmp5, Bmp4 and Tsg expression and Smad1/5/8 activity.…”
Section: Towards An Understanding Of the Molecular Mechanisms Involvesupporting
confidence: 54%
See 1 more Smart Citation
“…The identification of such a programme could improve our understanding of the HOXA2 mutant phenotype in humans. Indeed, we have shown that Hoxa2 regulates the expression of Eya1, which is involved in the branchio-oto-renal syndrome in humans (Abdelhak et al, 1997;Kochhar et al, 2007). Our functional and molecular analyses also reveal that Hoxa2 is involved in the regulation of Bmp5, Bmp4 and Tsg expression and Smad1/5/8 activity.…”
Section: Towards An Understanding Of the Molecular Mechanisms Involvesupporting
confidence: 54%
“…Bmp5 inactivation results in a small pinna [known as the short ear mutation (King et al, 1994;Kingsley et al, 1992)], and we further show that Bmp4 conditional inactivation also partially impairs pinna development. Moreover, Hoxa2 regulates the expression of eyes absent 1 (Eya1), which in humans is involved in the branchio-otorenal syndrome (Abdelhak et al, 1997;Kochhar et al, 2007). Thus, Hoxa2 is a fundamental transcriptional regulator orchestrating the morphogenesis of the auricle.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of 2 genes, EYA1 and SIX1, are known to cause the BOR phenotype, with EYA1 mutations accounting for approximately 40% of cases. 4 Hearing impairment occurs in 70%-93% of individuals with BOR syndrome, with the age of onset varying from early childhood to young adulthood. Hearing loss may be conductive, sensorineural, or mixed and may range from mild to profound.…”
Section: Bor Syndromementioning
confidence: 99%
“…Hearing loss may be conductive, sensorineural, or mixed and may range from mild to profound. 4 Inner ear anomalies seen in BOR syndrome include cochlear hypoplasia, particularly involving the apical turn; deviation of the labyrinthine facial nerve canal medial to the cochlea (Fig 1); and a funnel-shaped IAC with a large porus acousticus. 5 Vestibular dysplasia, SCC hypoplasia, enlargement of the vestibular aqueduct, and cochlear nerve deficiency are also reported.…”
Section: Bor Syndromementioning
confidence: 99%
“…Some syndromic forms of preauricular sinuses are frequently associated with renal malformations and hearing defects. Preauricular sinus and hearing loss are the most common features observed in patients with branchio-oto-renal (BOR) syndrome (OMIM 113650 and 610896) and the allelic branchio-otic (BO) syndrome (OMIM 602588 and 608389) [Smith and Schwartz, 1998;Kochhar et al, 2007]. Besides BOR/BO, other syndromes with overlapping phenotypes such as oto-facial-cervical syndrome (OMIM 166780), Townes-Brocks syndrome (OMIM 107480), and branchio-oculo-facial syndrome (OMIM 113620) also manifest varying degrees of preauricular sinus and hearing loss.…”
Section: Introductionmentioning
confidence: 99%